Solubility of Iridium and Ruthenium Organometallic Photoredox Catalysts - Jespersen, Daniel (Org Process Res Dev, 2019)
Despite the exponential growth of the field of photocatalysis, for reasons that are not entirely clear, these precious photocatalysts are often used in the literature at loadings that exceed their maximum solubility. On an industrial scale, the quantity of any precious metal catalyst can be a substantial financial burden or a sourcing issue, not to mention concerns as to the ecological and earth abundance of these catalysts. We believe that inattention to solubility has made these reactions appear less efficient than they actually are, because much of the photocatalyst remains undissolved. Therefore, the maximum solubilities of iridium and ruthenium centered photocatalysts have been systematically identified in industrially relevant solvents. Further, a literature photocatalytic reaction which our results suggested was beyond the maximum solubility has been revisited, with interesting results.